Microbiological quality evaluation of ready-to-eat foods at the mass event Rock in Rio 2022, Rio de Janeiro, Brazil - MENDES, Ariane Marinho; FORSYTHE, Stephen; BRANDÃO, Marcelo Luiz Lima (Food Science and Technology, 2024)
Food-borne diseases are a global concern, exacerbated by unchecked urbanization and population growth. They have a significant impact on public health and economy. Brazil, known for its vibrant mass events, such as the Rock in Rio festival, presents a unique challenge concerning food safety. This study focused on the microbiological assessment of ready-to-eat foods at the 2022 9th Rock in Rio mass event. Over the seven event days, 102 ready-to-eat food samples from the 30 vendors at the festival were collected. The foods were assessed according to the Brazilian Resolution No. 724/2022 and Normative Instruction No. 161/2022. Microbiological analysis revealed ten (9.80%) samples were unsatisfactory and three (2.94%) had intermediate safety. Escherichia coli, Bacillus cereus, and coagulase-positive Staphylococcus were among the predominant microorganisms identified. Although no foodborne disease outbreaks were associated with the Rock in Rio event, the attributed establishments incurred appropriate penalties in line with health regulations. The findings emphasize the risk associated with mass event food service practices. Overall, this study highlights the critical role of Health Surveillance in proactively ensuring public health during mass events and underscores the significance of disseminating these findings for improving future control measures in similar settings.